2006
DOI: 10.1152/ajpheart.00613.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Na+/Ca2+ exchanger in catecholamine-induced increase in intracellular calcium in cardiomyocytes

Abstract: Although sarcolemmal (SL) Na+/Ca2+ exchanger is known to regulate the intracellular Ca2+ concentration ([Ca2+]i), its involvement in catecholamine-induced increase in [Ca2+]i is not fully understood. To gain some information in this regard, isolated rat cardiomyocytes were treated with different agents, which are known to modify Ca2+ movements, in the absence or presence of a beta-adrenoceptor agonist, isoproterenol, and [Ca2+]i in cardiomyocytes was determined spectrofluorometrically with fura-2 AM. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
(76 reference statements)
2
32
0
1
Order By: Relevance
“…Magnesium deficiency, in particular when combined with stress and catecholamine secretion, might lead to enhanced entry of calcium into VSMC, which in turn can result in increased arteriolar tone and coronary spasm. Hypertension and its complications may also be the final consequences of increased calcium influx and contraction of VSMC [1,51] . Moreover, it was observed that magnesium acts on most types of calcium channels in VSMC exerting substantial arterial blood pressure-lowering properties, resulting in a reduction of peripheral and cerebral vascular resistance [37,52] .…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiency, in particular when combined with stress and catecholamine secretion, might lead to enhanced entry of calcium into VSMC, which in turn can result in increased arteriolar tone and coronary spasm. Hypertension and its complications may also be the final consequences of increased calcium influx and contraction of VSMC [1,51] . Moreover, it was observed that magnesium acts on most types of calcium channels in VSMC exerting substantial arterial blood pressure-lowering properties, resulting in a reduction of peripheral and cerebral vascular resistance [37,52] .…”
Section: Discussionmentioning
confidence: 99%
“…Severe hyponatremia also leads to intracellular accumulation of calcium due to functional disturbance of membrane sodium/calcium ion pumps, because, in addition to L-type calcium ion channels, the sodium/ calcium ion exchanger may play an important role in catecholamine-induced increases in intracellular calcium in cardiomyocytes [18]. Thus, cardiac sodium/ calcium ion exchange is critical in the regulation of cardiac myocyte calcium, and its altered function contributes to systolic dysfunction in heart failure and arrhythmogenesis [19].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the effects of Ca 2ϩ antagonists verapamil and diltiazem (38), as well as Na ϩ /Ca 2ϩ exchange inhibitors amiloride and KB- R7943 (38), on recovery of cardiac performance and mitochondrial function of the 30-min I/R hearts are shown in Table 3. Although the increased LVEDP in I/R hearts was significantly reduced by all these agents, both verapamil and amiloride further attenuated the recovery of depressed LVDP, whereas diltiazem and KB-R7943 had no effect on the recovery of depressed LVDP due to I/R.…”
Section: Duration Of Ischemia and Mitochondrial Functionmentioning
confidence: 99%